Analisis Faktor-Faktor Yang Mempengaruhi Dimensi Penyusun Indeks Pembangunan Manusia (IPM) Di Provinsi Sulawesi Utara - Parengkuan, Christian David; Katiandagho, Theodora Maulina; Ngangi, Charles Reijnaldo (Sam Ratulangi University, 2023)
This study aims to analyze the Pure Partisipation Rate of SD/MI and Gross Regional Domestic Product which affect the Education Dimension (Expected Years of Schooling) in North Sulawesi Province and to analyze the number of poor people and the open unemployment rate which affect the Expenditure Dimension (Decent Standard of Living) in North Sulawesi Province. This research was conducted from March to May 2023. The type of data used is secondary data from published reports produced by the North Sulawesi Central Statistics Agency for 2021. The objects in this study were 15 districts/cities in North Sulawesi province. The results of the study show that the Pure Partisipation Rate of SD/MI and Gross Regional Domestic Product simultaneously have an influence on the Old School Expectancy. The influence exerted by PPR SD/MI is 37.7% and GRDP is 25.8%. The number of poor people and the open unemployment rate simultaneously have an influence on per capita spending. The influence given by the number of poor people is 39.9% and the open unemployment rate is 45.8%.